A study on the withdrawal and reduced craving effect on the alcohol dependent patients with liver cirrhosis on calcium carbonates therapy.. - Akanshi, Ohri; Yogesh, Bansal; kumar, Shahi Rakesh (Journal of Neonatal Surgery, 2025)
Calcium seems to be the active ingredient in acamprosate (Ca₂⁺ bis-acetyl-homotaurinate), an anti-craving drug, based on research done before it was tested on people. Higher levels of calcium in the blood caused by taking acamprosate have also been linked to better results in terms of longer periods of abstinence and less time to relapse in human clinical trials. Conversely, alcohol craving was associated with diminished calcium levels in individuals with alcohol dependence. The primary objective of the research was to examine the withdrawal and diminished craving effects in alcohol-dependent patients with liver cirrhosis undergoing calcium carbonate therapy. A total of 78 alcohol-dependent participants received either calcium carbonate (400 mg + 10 μg vitamin D) or sodium bicarbonate (1,000 mg) daily for 28 days during inpatient alcohol withdrawal treatment. According to an intention-to-treat methodology, the calcium carbonate group had a faster decrease in withdrawal intensity (measured with CIWA-Ar) than the sodium bicarbonate subgroup. The calcium carbonate group had a much lower desire for alcohol (measured by OCDS) than the sodium bicarbonate group. Our research indicates that administering calcium carbonate to alcohol-dependent patients with liver cirrhosis during alcohol withdrawal mitigates both alcohol cravings and withdrawal symptoms. To facilitate the advancement of pharmacological therapies beyond Ca2+ bis-acetyl-homotaurinate, the mechanism of action must be elucidated